Home Economics as a foundation for life skills and livelihood - Gervacio, Ellen (PINAS GAZETTE: Essays, Stories & Poetry, 2025)
Home Economics equips individuals with practical competencies—from nutrition and budgeting to sewing and caregiving—that foster self-reliance, strengthen families, and open livelihood pathways. Especially in crises such as the COVID-19 pandemic, these life skills prove indispensable for household resilience. By integrating Home Economics into the Technical-Vocational Livelihood (TVL) track and aligning it with TESDA certifications, Philippine education can nurture entrepreneurship and community development.